2022
DOI: 10.3390/ijms232415757
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances in Mechanical Properties and Applications of Dual Network Hydrogels

Abstract: Hydrogels with a three-dimensional network structure are particularly outstanding in water absorption and water retention because water exists stably in the interior, making the gel appear elastic and solid. Although traditional hydrogels have good water absorption and high water content, they have poor mechanical properties and are not strong enough to be applied in some scenarios today. The proposal of double-network hydrogels has dramatically improved the toughness and mechanical strength of hydrogels that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Increases in the compressive modulus of the PEGDA-containing samples may be due to physical crosslinking of the crystalline domain of PEGDA 35 with the creation of a double network of GelMA and PEGDA hydrogels. 36 The improved mechanical properties of GelMA hydrogels by addition of PEGDA have been also reported by previous studies. 25,35,[37][38][39] Paper Biomaterials Science…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Increases in the compressive modulus of the PEGDA-containing samples may be due to physical crosslinking of the crystalline domain of PEGDA 35 with the creation of a double network of GelMA and PEGDA hydrogels. 36 The improved mechanical properties of GelMA hydrogels by addition of PEGDA have been also reported by previous studies. 25,35,[37][38][39] Paper Biomaterials Science…”
Section: Resultssupporting
confidence: 72%
“…This improved bioadhesive property of dCor/Gel-PEG in comparison to Gel-PEG hydrogel can be attributed to the formation of a double network following the rearrangement of triple precursor α-chains of digested collagen in dCor within the Gel-PEG hydrogels. 36 In addition, the presence of covalent bonds between -CH 2 in PEGDA and -NH 2 of lysine in digested proteins of dCor led to the formation of a Urethane Linkage, which is strongly responsible for the improved bioadhesiveness of this dual-network hydrogel to surrounding tissues. 41 Another key factor in designing corneal sealants is their transparency, as well as their ability to exchange nutrients, oxygen, and water within the sealant body.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of energy dissipation mechanisms often contributes to the excessive brittleness observed in conventional hydrogels. 26,27 Further, a heterogeneous network architecture arising from defects such as loops and dangling chains formed during the cross-linking process can lead to stress concentrations and catastrophic failure. 28−33 Despite an abundance of literature describing hydrogels as tissue scaffolds, the correlation between network connectivity and material performance is often overlooked in the tissue engineering field.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This involves primarily developing a nuanced understanding of their structure–property relationships. The absence of energy dissipation mechanisms often contributes to the excessive brittleness observed in conventional hydrogels. , Further, a heterogeneous network architecture arising from defects such as loops and dangling chains formed during the cross-linking process can lead to stress concentrations and catastrophic failure. Despite an abundance of literature describing hydrogels as tissue scaffolds, the correlation between network connectivity and material performance is often overlooked in the tissue engineering field . A deeper understanding of the network structure can provide us with valuable insights for addressing the factors responsible for the hydrogels’ mechanical deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, dual network (DN) hydrogels, first established in 2003 by Gong et al , 14 have been recently demonstrated to be effective in constructing flexible sensors possessing enhanced physicochemical properties and integrated multifunctionality. 15–18 For example, Li et al fabricated a tough DN hydrogel through combining thermoreversible κ-carrageenan hydrogel with polyacrylamide network, where the former rendered good recoverability and self-healing capability to the DN hydrogel while the latter enabled 3D printing by means of UV light-triggered photopolymerization. 19 Gu et al employed the host–guest interaction and dynamic covalent bond to prepare DN hydrogels, acquiring satisfactory comprehensive performance including stretchability, strength, remodeling ability, self-healing property, self-adhesiveness, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%